Pengaruh Permainan Cak n Cek Bangtar terhadap Hasil Belajar Siswa SD - Cahyaningtyas, Dwi; Wijayanto, Zainnur; Barriyah, Insanul Qisti (Lembaga Yasin AlSys, 2025)
Mathematics learning is often perceived as abstract and disconnected from students’ daily lives, which contributes to low interest and motivation to learn. This study aims to examine the effect of the traditional educational game Cak n Cek Bangtar on elementary school students’ mathematics learning outcomes in the topic of plane figures. The research employed a pre-experimental design with a one-group pretest-posttest model. The subjects were nine fourth-grade students at SD Negeri Gondangan, Jogonalan Subdistrict, Klaten. The instrument used was a learning outcome test, and the data were analyzed using normality testing, N-Gain analysis, and a paired sample t-test. The results show a significant improvement in learning outcomes following the implementation of the game. The average pretest score of 58.2 increased to 81.4 in the posttest. N-Gain analysis indicated a gain of 0.65, categorized as moderate. The t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. These findings demonstrate that the traditional game Cak n Cek Bangtar is effective as a contextual approach to mathematics learning, particularly in the topic of plane figures. The study concludes that integrating educational games rooted in Tamansiswa values can improve learning outcomes while creating an enjoyable and meaningful learning atmosphere. This research contributes to the development of innovative and relevant instructional strategies in primary education.